MEMBANGUN SOLIDARITAS PESERTA DIDIK MELALUI KEGIATAN BAKTI SOSAL ORGANISASI SISWA INTRA SEKOLAH - Kinasih, Kania Puspa; Dahliyana, Asep (Universitas Pendidikan Indonesia, 2018)
The aim of this study is to find out how the role of schools and organizations in it including the Intra School Social Organization (OSIS) in instilling social solidarity values to its members through social work activities conducted by OSIS in SMAN 5 Cimahi. This research uses qualitative approach with analytical descriptive method. Data were collected using interview technique, observation, documentation study, literature study, and field note. The result of the research shows that from social service activities conducted by OSIS in SMAN 5 Cimahi, able to build social solidarity inter students, it was seen from the social service activity contain elements of solidarity.